Work Motivation and Work Discipline on Teachers’ Performance in State Vocational Schools - Amini Amini; Marliani Marliani; Elfrianto Elfrianto; Isthifa Kemal (STAI Hubbulwathan Duri, 2022)
This study aims to determine the effect of work motivation and work discipline on the performance of State Vocational High School teachers throughout Central Tapanuli Regency. This study aims to determine the effect of motivation on the performance of State Vocational High School teachers throughout Central Tapanuli Regency. This study aims to determine the effect of discipline on the performance of State Vocational High School teachers in the Central Tapanuli Regency. To determine the effect of motivation and work discipline together on the performance of State Vocational High School teachers throughout Central Tapanuli Regency. The population in this study were all teachers of State Vocational Schools in Central Tapanuli Regency, North Sumatra Province as many as 99 people. From the results of the study, it can be seen that the results are For that can the coefficient of determination, work motivation variable influence (X1) to the variable teacher performance in SMK Se-Central Tapanulii(Y) R Square is 95.5%. This means that the work motivation variable (X1) has an influence on variable teacher performance at State Vocational Schools throughout Central Tapanuli Regency (Y) of 95.5%. While was discussion results study influence the discipline of work with the teacher's performance can see of the calculation results explain that the influence between the variable work discipline (X2) on teacher performance (Y) with the value of is significant 0.000.05. While was can know the value of the coefficient of determination (contributions) the impact of work discipline variables (X2) to teacher performance (Y) R Square of 89.1%. work discipline means that the variables (X2) on teacher performance (Y) for 89.1%. And simultaneous testing influences work motivation, work discipline to variable teacher performance The SMK Se-Central Tapanuli is can know that value coefficient determination work motivation variable (X1), work discipline (X2) it simultaneously (together) variable teacher performance (Y) seen in column R square that for 96.1% means work motivation (X1), work discipline (X2) as together have influence to variables the performance of teachers-Centralin SMK in Tapanuli for 96.1%.